Spectrum of elective pancreatic surgeries with short term outcomes at a tertiary hospital in North India - Rana, Hema; Ray, Jitendra Prasad; Rehmani, Babar (International Surgery Journal, 2020)
Background: Pancreatic surgeries have undergone substantial changes over the last few decades and are now being attempted by many surgeons not limited to specialised centres. The study has attempted to document the indications for elective pancreatic surgeries and its outcomes in terms of morbidity and mortality. Methods: This observational study included 42 patients over a period of 12 months. The data were recorded in a predesigned proforma to assess the indication for elective pancreatic surgery, to describe the number and kind of pancreatic operation undertaken and to evaluate the short-term outcome of various pancreatic surgeries in terms of complications, morbidity and mortality. Results: Authors studied 42 patients, who underwent the elective pancreatic surgeries for various indications in hospital. Histopathological studies revealed that the majority (50%) were carcinoma of the head of pancreas. Pancreaticoduodenectomy (PD) was done in all the sixteen cases. The most important complications of PD were delayed gastric emptying (DGE) (50%), surgical site infection (SSI) (43.7%), post pancreatic haemorrhage (PPH) (31%), post-operative pancreatic fistula (POPF) (25%) and intra-abdominal abscess (IAA) (12.5%). Of the 26 patients operated for benign conditions of pancreas, 19 (73%) had pancreatic pseudocyst, in majority of cases as a sequela of alcohol induced pancreatitis. Partington Rochelle procedure was the commonest surgical procedure in chronic pancreatitis. Conclusions: Carcinoma of head of pancreas was the most common periampullary malignancy necessitating major pancreatic resections. DGE, POPF and PPH were the most common and significant post-operative complications.